Jane Eyre movie: illocutionary acts in focus and its contribution to English language teaching - Hidayatusyifa Nuzula (Erudita: Journal of English Language Teaching, 2023)
The objectives of this research are to showcase 1) the types of Illocutionary act found in the Jane Eyre movie, 2) the most dominant type of the Illocutionary acts, and 3) the contributions of the illocutionary acts in teaching English. This research is descriptive qualitative where the researcher presents the result of the research in the form of description. The data collection followed some procedures: downloading the movie, watching the movie, reading the script repeatedly, finding illocutionary acts, and taking the collected illocutionary act into the note. In analyzing the collected data, descriptive analysis technique was applied by the researcher. The study findings demonstrate that there are the entire five types of illocutionary acts. From the total 19 utterances which contain illocutionary act, there were 5 utterances belong to assertive, 4 utterances belong to directive, 4 utterances belong to expressive, 3 utterances belong to commissive, and 3 utterances belong to declarative illocutionary act. The most dominant type of illocutionary acts performed by the characters of the Jane Eyre movie is assertive. In addition, the result of this research can contribute to the use of instructional media in English language teaching.